ANTIOXIDANT, ANTIMICROBIAL, TYROSINASE ENZYME INHIBITION AND CHEMICAL COMPOSITIONS OF SHALLOT EXTRACTS - Charoenchai, Laksana; Settharaksa, Sukanya; Sueree, Lukman; Wunnakup, Thaniya; Phetmanee, Thidarat; Lukkunaprasit, Thitiya; Meksuriyen, Duangdeun (Interprofessional Journal of Health Sciences, 2023)
Shallot (Allium ascalonicum L.) was in the same genus as garlic and onion. These plants exhibit some activities; however, more studies need to be conducted to evaluate the activities of ethanolic shallot extracts. The objectives of this study were to prepare shallot extracts, evaluate their safety, and determine their antimicrobial, antioxidant and anti-tyrosinase activities. Shallot bulbs were extracted with water and 20-95% ethanol concentration. The antioxidant activity was determined using DPPH radical scavenging assay and anti-tyrosinase activity was evaluated using enzyme assay technique. Disc agar diffusion method and broth micro-dilution method were used to determine antimicrobial properties of shallot extracts against S. aureaus, S. epidermis and P. acne. The toxicity of the extracts was assessed using MTT assay on primary human dermal fibroblast (HDF) cells. Chemical compositions of shallot extracts were examined using HPLC analysis. The results showed that 20% ethanolic shallot extract exhibited the highest quercetin equivalent and the highest antioxidant activity. In contrast, 80% ethanolic shallot extracts showed the highest tyrosinase inhibition. Shallot extracts were not toxic to HDF cells at the concentration lower than 20 mg/mL. They did not have antimicrobial activity against tested bacteria in this study. HPLC analysis showed elution pattern of flavonol glucosides similar to methanolic onion and shallot extracts. This result suggests that ethanol concentration may involve in the chemical compositions of shallot extract and resulting in various antioxidant activity. Some flavonol glucosides may be responsible for the activities of shallot extracts. However, antimicrobial and anti-tyrosinase enzyme activity may relate to other substances in shallot extracts.